The Changes in Social Commitment in The Works of Haruki Murakami - Dian Annisa Nur Ridha (MOZAIK HUMANIORA, 2023)
Haruki Murakami's early works, including "Hear The Wind Sing" and "Norwegian Wood," depict main characters characterized by a sense of detachment from society, reflecting the prevailing sentiments among Japanese youth in the late 1960s and 1970s. However, a notable shift occurs in Murakami's writing after 1995, particularly evident in novels like "The Wind-Up Bird Chronicle," where the initial detachment transforms into a more engaged narrative. This research employs dialectical analysis, drawing from Murakami's aforementioned literary works   and connecting them with his background, as revealed in the non-fiction piece "Underground," along with the social context of their creation. The objective is to explore the evolution of social commitment in Murakami's works, revealing a transition from detachment to attachment, and from themes of death and alienation to those of exploration and understanding. The newfound attachment serves a broader purpose: an understanding that transcends individual characters, fostering a connection among all human beings.